Not now but later - a qualitative study of non-exercising pregnant women's views and experiences of exercise - Maria Ekelin; Mette Langeland Iversen; Mette Grønbæk Backhausen; Hanne Kristine Hegaard (BMC, 2018)
Abstract Background Evidence has shown that there are several physical and mental advantages of exercise during pregnancy. Despite this, the recommendations for exercise during pregnancy are poorly fulfilled. The aim of this study was to illuminate non-exercising pregnant women's views and experiences concerning exercise before and during pregnancy. Method The study had a qualitative design with an inductive approach and was analysed by content analysis. A total of 16 individual and face-to-face interviews were conducted with healthy pregnant women, mainly in the third trimester and living in Sweden. The participating women had not been exercising 3 months before pregnancy or during pregnancy. Results The main category "Insurmountable now, but possible in the future" was based on the four categories: "Lost and lack of routines", "Feelings of inadequacy", "Having a different focus" and "Need for support". The women experienced that their lack of routines was a major barrier that prevented them from exercising. Other factors that contributed were, for example, pregnancy-related problems, long working days and prioritizing family life. The women described it as difficult to combine exercise with their focus on the pregnancy and they missed continuous support from the antenatal care provider. The women expressed a need for suggestions concerning exercise during pregnancy and follow-up on previous counselling, especially when pregnancy-related issues arose. Information about easily accessible alternatives or simple home exercises was requested. They felt immobile and were not satisfied with their inactivity and tried to partly compensate with everyday activities. The women identified the postpartum period as an important possibility for becoming more active, for their own sake, but also because they wanted to become role models for their children. Conclusion Continuous support during pregnancy is needed concerning exercise. Pregnancy is mostly a barrier that prevents exercise for this group of women but, at the same time, may be a motivator and a possibility for better health. As the result showed that these women were highly motivated to a life-style change post-pregnancy, it may be crucial to support previously non-exercising women postpartum.